TINGKAT KEPUASAN KELUARGA BERPENDAPATAN RENDAH TERHADAP SUMBERDAYA YANG DIMILIKI - Kusumo, Rani Andriani Budi; Simanjuntak, Megawati (Jurnal Ilmu Keluarga dan Konsumen, 2009)
Family function as a system is very urged by what to be the aims of life and ownership of resources. Family’s aims can be reached when resources available. Satisfaction level on family’s resources ownership is influenced by family’s values. The aimed of this research were to identify the ownership of resources of low income family and to analyze the satisfaction level on resources ownership by low income family. This research was a cross sectional study in thirty poor families that lived in urban area. In low income family, resources ownership (especially physical resources) is limited. Average of income per capita per month was Rp 78.492,00. Income was used only for daily food consumption, just enough "to eat" and not considering family nutrient requirement aspects. Because of this economy limitedness, many families had childrens who dropped out school. In general, physical resources that owned by family can only fulfil half of samples’ expectation, while non physical resources factor in general can fulfil samples’ expectation. Samples’s age correlated positively with the satisfaction level, while education correlated negatively with satisfaction level. Family income not correlated with samples satisfaction level. Satisfaction was influenced by how the families managed the income to fulfill daily needs.